The Association Between Medication Adherence, Internalized Stigma and Social Support Among Outpatients with Major Depressive Disorder in a Malaysian Hospital: A Cross-Sectional Study - Halim R; Kaur M; Syed Mokhtar SS; Chemi N; Sajatovic M; Tan YK; Siau CS; Ng CG (Psychology Research and Behavior Management)
Rahilah Halim,1,* Manveen Kaur,2,* Sharifah Suziah Syed Mokhtar,1 Norliza Chemi,1 Martha Sajatovic,3 Yee Kee Tan,4 Ching Sin Siau,4 Chong Guan Ng2 1Department of Psychiatry and Mental Health, Hospital Kajang, Kajang, Selangor, Malaysia; 2Psychological Medicine Department, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur, Malaysia; 3Neurological and Behavioral Outcomes Center, University Hospital Cleveland Medical Center & Case Western Reserve University School of Medicine, Cleveland, OH, USA; 4Centre for Community Health Studies (Reach), Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur, Malaysia*These authors contributed equally to this workCorrespondence: Manveen Kaur, Psychological Medicine Department, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur, Malaysia, Email manveen@um.edu.my Ching Sin Siau, Centre for Community Health Studies, Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Kuala Lumpur, Wilayah Persekutuan, Malaysia, Email chingsin.siau@ukm.edu.myBackground: Internalized stigma and medication non-adherence pose significant challenges for treating major depressive disorder (MDD), leading to disability, increased suicide risk, and morbidity. Limited data exists on modifiable factors associated with adherence in lower-resourced settings like Malaysia. This study aimed to investigate poor adherence prevalence and the demographic and clinical factors associated with poor medication adherence among patients with MDD.Methods: This cross-sectional survey recruited participants using universal sampling from a major hospital in Selangor, Malaysia. Participants answered questionnaires consisting of demographic and clinical information (medical history, duration of anti-depressant treatment for MDD, psychiatric ward admission history, and any medication side effects experienced), the Internalized Stigma of Mental Illness Scale (comprising alienation, stereotype, perceived discrimination, and social withdrawal), the Multidimensional Scale of Perceived Social Support (comprising family, friend, and significant other support), and the Malaysia Medication Adherence Assessment Tool. Simple and multiple logistic regression and mediation analyses were conducted.Results: Of the 268 participants (69% female), 57.1% were suboptimally or moderately adherent to their medication. Buddhists (adjusted odds ratio [aOR] = 0.280, 95% CI [0.115, 0.679], p = 0.005), higher family support (aOR = 0.753, 95% CI [0.591, 0.960], p = 0.022), a history of ward admissions (aOR = 3.523, 95% CI [1.537, 8.072], p = 0.003), and higher internalized stigma (aOR = 2.828, 95% CI [1.497, 5.344], p = 0.001) were significantly associated with low/moderate medication adherence. The effect of internalized stigma subdomains (alienation, perceived discrimination, and social withdrawal) on medication adherence were partially mediated by family support.Conclusion: More than half of the participants demonstrated low to moderate medication adherence. Those with higher internalized stigma demonstrated higher odds of low/moderate medication adherence, but this effect was attenuated by family support. Therefore, internalized stigma and family support are important points of consideration when assessing patients with MDD in Malaysia.Keywords: medication adherence, MDD, internalized stigma, social support, Malaysia